ЗАМАН ҚАҲАРМАНЫ ОБРАЗЫ - Шержанова, Ф.К. (FAN va JAMIYAT, 2018)
The article deals with the issues of theatre life. It is devoted to «striving for success» (Интилганга толе ёр) which was staged at the Karakalpak State academic theatre. The author describes the image of the main character in the drama. On the examples the author studies the dramatist’s skill in creating heroic images and their similarities with other personages in the drama.